Inside Back Cover: Pressure‐Responsive Two‐Dimensional Metal–Organic Framework Composite Membranes for CO2 Separation (Angew. Chem. Int. Ed. 20/2021). Issue 20 (30th March 2021) - Ying, Yunpan; Zhang, Zhengqing; Peh, Shing Bo; Karmakar, Avishek; Cheng, Youdong; Zhang, Jian; Xi, Lifei; Boothroyd, Chris; Lam, Yeng Ming; Zhong, Chongli; Zhao, Dan
Abstract : Stimuli‐responsive phenomena are widely observed in nature. In their Research Article on page 11318, Chongli Zhong, Dan Zhao, and co‐workers report for pressure‐responsive metal–organic framework (MOF) composite membranes based on the gate‐opening effect that CO2 molecules act as a "key" to open the MOF gates. Huge jumps of CO2 permeance as well as CO2 /N2 and CO2 /CH4 selectivities occur above the gate‐opening pressure of the flexible MOF, demonstrating a smart gas separation behavior.